(untitled) - Laudicina, Paul A. (Hoboken, N.J., 2012)
Change is essential, and in this book, A.T. Kearney CEO Paul Laudicina takes a behind-the-scenes look at the people and institutions that are thinking big to repair the international social fabric and help pave the way for a better future so that you can follow in their footsteps. Showing you where to look for new insights and ideas, how to widen your lens, and why you need to master scenario planning in order to make sense of today's world, Laudicina presents a comprehensive and insightful look into the information overload threatening businesses everywhere and how you can fight back.
Keywords: Strategic planning,Hoạch định chiến lược